Testing hypotheses about the function of repeated nest abandonment as a life history strategy in a passerine bird. (11th March 2016) - Beckmann, Christa; Martin, Kathy
Abstract : Nest structures are essential for successful reproduction in most bird species. Nest construction costs time and energy, and most bird species typically build one nest per breeding attempt. Some species, however, build more than one nest, and the reason for this behaviour is often unclear. In the Grey Fantail Rhipidura albiscapa, nest abandonment before egg‐laying is very common. Fantails will build up to seven nests within a breeding season, and pairs abandon up to 71% of their nests before egg‐laying. We describe multiple nest‐building behaviour in the Grey Fantail and test four hypotheses explaining nest abandonment in this species: cryptic depredation, destruction of nests during storm events, and two anti‐predatory responses (construction of decoy nests to confuse predators, and increasing concealment to 'hide' nests more effectively). We found support for only one hypothesis – that abandonment is related to nest concealment. Abandoned nests were significantly less concealed than nests that received eggs. Most abandoned nests were not completely built and none received eggs, thus ruling out cryptic predation. Nests were not more likely to be abandoned following storm events. The decoy nest hypothesis was refuted as abandoned nests were constructed at any point during the breeding season and some nests were dismantled and the material used to build the subsequent nest. Thus, Grey Fantails are flexible about nest‐site locations during the nest‐building phase and readily abandon nest locations if they are found to have deficient security.